(untitled) (Journal of Human Sciences, 2021)
The Fezzan site in the Libyan desert represented an important center and link between the different regions that have to pass through it to reach each other, such as the eastern regions in Egypt and northern Africa, which are continuing with Europe and the central and western African continent, and despite the harshness of the desert, the desert oases acted as a coolant to the atmosphere and to enhance the communication process For convoys passing through them to all parts of the continent, where they formed a safe haven, which earned the continent an important place in the process of connecting all its destinations. North Africa and sub-Saharan Africa are two economically complementary regions, and the Libyan oases - such as: Awjila, Gallo, Kufra, Murzuq, Ghat, Ghadames ... and others - played an important role in the communication process and in stimulating trade exchange. What interests us here is the study of oases located within the Fezzan region and their taking the role of commercial terminals for caravans crossing the Sahara, thanks to which the cities in their path and within the region itself developed. Traveler’s books and historical sources talk about the existence of economic relations between the northern regions of the continent and central Africa in the period of the Islamic era, which was a direct reason for its prosperity after the conquest of Egypt and North Africa. The roads through Fezzan were the main routes for the delivery of Sudanese goods, most notably slaves, towards North Africa and Egypt